A taxonomic treatment of Trisetopsis (Poeae, Poaceae) in southern Africa - Mashau, Aluoneswi C.; Fish, Lyn; van Wyk, Abraham E. (Phytotaxa, 2020)
Trisetopsis, a genus of temperate C3 grasses, extends from the Arabian Peninsula southwards along the African mountains (temperate Afromontane Region) to sub-Saharan Africa and Madagascar, with a centre of diversity in southern Africa. A taxonomic treatment of Trisetopsis in the Flora of southern Africa (FSA) region is presented. The proposed classification is based on existing and comparative evidence derived from macromorphology, micromorphology, leaf anatomy, DNA sequences and geographical distribution. Fourteen species of Trisetopsis are recognized in the FSA region, all of them endemic to the region. Five of the species are rare; based on IUCN Red List categories and criteria, three species are considered “Vulnerable”, one as “Endangered, and one as “Critically Endangered” and probably “Extinct”. Improved and emended species descriptions, a key to the species, updated distribution maps and illustrations, especially of the spikelets, are provided. Lectotypes are designated for the names Avenastrum longum var. grande and Avena longa (basionym of Trisetopsis longa).